The Reality of Professional Competency of Kindergarten Teachers in Banda Aceh Through the Use of Headmaster’s Academic Supervision - Nurhafni, Nurhafni; Niswanto, Niswanto; Murniati, Murniati; Zakaria, Nurhijrah Binti (JETL (Journal of Education, Teaching and Learning), 2025)
This study aimed to identify academic supervision including planning, implementation, evaluation, and follow-up process which had been done by the headmaster to improve the professional competency of kindergarten teachers in Banda Aceh. Descriptive qualitative had been used as an approach in this research. Observation, interview, and documentation were used as collecting data techniques.  The data were analyzed by using descriptive qualititave with along with data reduction strategies, data visualization, and conclusion drawings. The research's conclusions revealed that: (1) the headmaster plans the academic supervision program to enhance learning and carries it out both inside and outside of the classroom;(2) Academic supervision is implemented in stages, starting with pre-observation, observation, evaluation, and follow-up, or problem-solving; (3)Individual and group evaluations are conducted regarding academic supervision. and (4) The outcomes of academic monitoring are further strengthened and improved, already meeting the requirements for teachers. The chance to attend training or grading is provided, as well as coaching and improvement for supervisory actions that have not yet reached the requisite standards.